167k views
5 votes
1) 3(3x - 4) = -2(1 – 4x)

2 Answers

4 votes

Answer:

x = 10

Explanation:

3(3x - 4) = -2(1 - 4x)

9x - 12 = -2 + 8x

9x - 8x = -2 + 12

x = 10

Hope this helps!

User Aaron Averett
by
5.0k points
2 votes
Let's solve your equation step-by-step.
3
(
3
x

4
)
=

2
(
1

4
x
)
Step 1: Simplify both sides of the equation.
3
(
3
x

4
)
=

2
(
1

4
x
)
(
3
)
(
3
x
)
+
(
3
)
(

4
)
=
(

2
)
(
1
)
+
(

2
)
(

4
x
)
(Distribute)
9
x
+

12
=

2
+
8
x
9
x

12
=
8
x

2
Step 2: Subtract 8x from both sides.
9
x

12

8
x
=
8
x

2

8
x
x

12
=

2
Step 3: Add 12 to both sides.
x

12
+
12
=

2
+
12
x
=
10
User Kaskasi
by
5.0k points